No use : nuclear weapons and U.S. national security - Nichols, Thomas M., 1960- (University of Pennsylvania Press, 2014)
In No Use, national security scholar Thomas M. Nichols examines the role of nuclear weapons and their prominence in U.S. security strategy, ultimately arguing that this belief in the utility of nuclear force is misguided and dangerously obsolete.
Keywords: Nuclear weapons -- Government policy -- United States.; National security -- United States.; United States -- Military policy.; Nuclear disarmament -- United States.; Security, International.; Armes nucléaires -- Politique gouvernementale -- États-Unis.; Désarmement nucléaire -- États-Unis.; POLITICAL SCIENCE -- Security (National & International); Military policy; National security; Nuclear disarmament; Nuclear weapons -- Government policy; Security, International; United States; Political Science.; Public Policy.